연결된 잔혹성: 혐오와 재미 사이의 길고양이 학대와 ‘인터넷 놀이 문화’ 공모 범죄 [Networked Cruelty: Hate-based, Fun-centered Animal Cruelty and Playful Complicity on the Internet] - Lee, Jin (2022)
This study is based on my 4 year-long digital ethnography on animal cruelty on the internet. Animal cruelty is social crime that has a long history across the globe. Notably, today’s animal cruelty is widely and popularly shared and consumed through social media, online communities, and social messenger apps, which has developed almost as a ‘new play culture’ on the web. I situate the growing popularity and demands for animal cruelty content on the internet, as evidenced in the increasing cases of torturing stray cats, within the contexts of online sensationalism and hate discourse/culture in South Korea. I consider online animal cruelty as a new internet vernacular culture, stemming from online misogyny in South Korea. I argue that the online animal cruelty culture is a networked complicity, originating in the hate culture and fragile masculinity today, which has risen as backlash against increasing visibility of feminism and discussion around gender equity in the Korean society. The networked complicity further expands across the online space and becomes popularized, encouraging anonymous others’ participation for fun, based on online anonymity and networkedness, while its criminality is overshadowed and dismissed. I conclude the paper by emphasizing an urgent need for the government, industry, media, and academics to take actions to stop the increasingly violent online hate/ torture culture.